Financial intelligence : a manager's guide to knowing what the numbers really mean - Berman, Karen; Knight, Joe ;Case, John (Boston, Massachusetts : Harvard Business Review Press, 2013)
"Inc." magazine calls it one of "the best, clearest guides to the numbers" on the market. Readers agree, saying it's exactly "what I need to know" and calling it a "must-read" for decision makers without expertise in finance. Since its release in 2006, "Financial Intelligence" has become a favorite among managers who need a guided tour through the numbers--helping them to understand not only what the numbers really mean, but also why they matter.
Part I. The art of finance (and why it matters) : You can't always trust the numbers -- Spotting assumptions, estimates, and biases -- Why increase your financial intelligence? -- The rules accountants follow: and why you don't always have to -- Part I toolbox : Getting what you want; The players and what they do; Reporting obligations of public companies -- Part II. The (many) peculiarities of the income statement: Profit is an estimate -- Cracking the code of the income statement -- Revenue: the issue is recognition -- Costs and expenses: no hard-and-fast rules -- The many forms of profit -- Part II toolbox : Understanding variance; Profit at nonprofits; A quick review: "percent of" and "percent change" -- Part III. The balance sheet reveals the most : Understanding balance sheet basics -- Assets: more estimates and assumptions (except for cash) -- On the other side: liabilities and equity -- Why the balance sheet balances -- The income statement affects the balance sheet -- Part III toolbox : Expense? Or capital expenditure?; The impact of mark-to-market accounting -- Part VI. Cash is king : Cash is a reality check -- Profit [does not equal] cash (and you need both) -- The language of cash flow -- How cash connects with everything else -- Why cash matters -- Part IV toolbox : Free cash flow; Even the big guys can run out of cash -- Part V. Ratios: learning what the numbers are really telling you : The power of ratios -- Profitability ratios: the higher the better (mostly) -- Leverage ratios: the balancing act -- Liquidity ratios: can we pay our bills? -- Efficiency ratios: making the most of your assets -- The investor's perspective: the "big five" numbers and shareholder value -- Part V toolbox : Which ratios are most important to your business?; The power of percent of sales; ratio relationships; Different companies, different calculations -- Part VI: How to calculate (and really understand) return on investment : The building blocks of ROI -- Figuring the ROI: the nitty-gritty -- Part VI toolbox : A step-by-step guide to analyzing capital expenditures; Calculating the cost of capital; Economic value added and economic profit-putting it all together -- Part VII. Applied financial intelligence: working capital management : The magic of managing the balance sheet -- Your balance sheet levers -- Homing in on cash conversion -- Part VII toolbox : Accounts receivable aging -- Part VIII. Creating a financially intelligent company : Financial literacy and corporate performance -- Financial literacy strategies -- Financial transparency: our ultimate goal -- Part VIII toolbox : Understanding Sarbanes-Oxley -- Appendix: Sample financials.
Includes index.
Keywords: CASH MANAGEMENT